Association Between Low Serum Testosterone and the Development of Metabolic Syndrome in Elderly Taiwanese Men - Zhong SR (Dove Medical Press, 2021)
Shang-Rong Zhong,1 Han-Hsuan Yang,1– 3 Cheng-Hsi Liao,4– 7 Deng-Ho Yang,5,6,8,9 Shih-Kai Tu,1,5 Chia-Lien Hung,6 Chun-Cheng Liao1,5,6 1Department of Family Medicine, Taichung Armed Forces General Hospital, Taichung, Taiwan; 2Department of Occupational Medicine, Taichung Veterans General Hospital, Taichung, Taiwan; 3School of Professional Education and Continuing Studies, National Taiwan University, Taipei, Taiwan; 4Division of Urology, Department of Surgery, Taichung Armed Forces General Hospital, Taichung, Taiwan; 5School of Medicine, National Defense Medical Center, Taipei, Taiwan; 6Department of Medical Education and Research, Taichung Armed Forces General Hospital, Taichung, Taiwan; 7Graduate Institute of Biomedical Science, China Medical University, Taichung, Taiwan; 8Division of Rheumatology/Immunology/Allergy, Department of Internal Medicine, Taichung Armed Forces General Hospital, Taichung, Taiwan; 9Department of Medical Laboratory Science and Biotechnology, Central Taiwan University of Science and Technology, Taichung, TaiwanCorrespondence: Chun-Cheng Liao Email milkbottle97@yahoo.com.twPurpose: To assess the association between serum testosterone (T) and metabolic syndrome (MS) in different age groups in Taiwanese men.Materials and Methods: Male participants, regardless of age or any underlying disease, were identified from MJ Health Screening Center in Taiwan from 2007 to 2016 for this cross-sectional study. They were divided into three groups according to age, and further classified according to MS diagnosis. Basic patient characteristics with relevant parameters were obtained. One-way ANOVA of mean T values between different numbers of measures that exceeds the cut-off values of MS components was performed to assess the relationship of T and MS. Logistic regression analysis was also used to estimate the risk for MS with each increment in T, age, and BMI.Results: A total of 4,931 men were included. The MS group had significantly lower serum T levels compared to the non-MS group in each age group. The one-way ANOVA found the mean value of T was significantly higher in patients without MS component (6.19± 2.12 ng/mL) than those with 1– 5 MS components (with one MS component: 5.48± 2.13 ng/mL, two MS components: 4.93± 2.03 ng/mL, three MS components: 4.37± 1.60 ng/mL, four MS components: 4.13± 2.89 ng/mL, five MS components: 3.74± 1.27 ng/mL, and P< 0.001). There was no significant difference between the patients with three components and the patients with four or five components. Logistic regression models with age stratification showed T with lower odds ratio (OR) for MS after adjusting for BMI in those ≥ 65 years old (OR=0.693; 95% CI=0.559– 0.858; P< 0.001); 50– 64 years old (OR=0.868; 95% CI=0.802– 0.940; P< 0.001) and < 50 years old (OR=0.810; 95% CI=0.758– 0.865; P< 0.001).Conclusion: Lower serum T was strongly associated with MS, with the predictive value increasing with age in Taiwanese men.Keywords: testosterone, metabolic syndrome, hypogonadism, insulin resistance